PREVALENCE OF MALIGNANCY IN GOITRE-A REVIEW OF 718 THYROIDECTOMIES - Haq, Raja Najum ul; Khan, Basharat Ali; Chaudhry, Ishtiaq Ahmed (Journal of Ayub Medical College Abbottabad, 2009)
Background: Thyroid malignancies are a heterogeneous group of tumours which show considerable variability in biological behaviour, histological appearances and response to therapy. Thyroid cancer is uncommon and represents only 1% of all malignancies. Objective was to determine the prevalence of malignancy in patients presenting with goitre. This prospective, observational study was conducted at Department of Surgery, Fauji Foundation Hospital, Rawalpindi from January 1999 to December 2008. Methods: All patients requiring surgery for goitre were included in the study. Postoperatively histopathologies of specimens were evaluated in all patients. Results: 718 patients were operated and post operative histopathology specimens were reviewed. 2.92% of patients were found to have malignancy. Prevalence of papillary and follicular carcinoma was 33.33% each. Anaplastic carcinoma was found in 23.81% of patients followed by Hurthle cell carcinoma in 9.53% of patients. Conclusion: All postoperative thyroid specimens should be subjected to histopathology. Prevalence of follicular carcinoma and anaplastic carcinoma is relatively higher in our country due to high incidence of iodine deficiency goitre. Keywords: Goitre, Malignancy, Prevalence, Carcinoma Thyroid